2009
DOI: 10.1080/10826070902841786
|View full text |Cite
|
Sign up to set email alerts
|

Column Classification and Selection for the Determination of Antibiotics by Micellar Liquid Chromatography

Abstract: Seven commercially available: Zorbax C 18 , Kromasil C 18 , C 8 , cyano, phenyl, monolithic and amino stationary phases columns, have been characterized and classified into broadly similar types to simplify column choice. The results were evaluated employing cluster analysis, which shows several interesting groups based on distances (Minkowski and Euclidean) in agreement with the manufacturer's claims: chain density of the stationary phase used, and the presence or not a silica base. Finally, results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…According to literature, aminopropyl columns are widely used, especially in hydrophilic interaction liquid chromatography. They also offer a more reactive, selective and efficient stationary phase and polar interactions are more abundant than in cyanopropyl columns (Gama et al, ; Rambla‐Alegre et al, ). Also aminopropyl columns offer the possibility of anion exchange mechanisms around neutral pH (Olsen, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to literature, aminopropyl columns are widely used, especially in hydrophilic interaction liquid chromatography. They also offer a more reactive, selective and efficient stationary phase and polar interactions are more abundant than in cyanopropyl columns (Gama et al, ; Rambla‐Alegre et al, ). Also aminopropyl columns offer the possibility of anion exchange mechanisms around neutral pH (Olsen, ).…”
Section: Resultsmentioning
confidence: 99%
“…Different stationary phases have different chemical characteristics which influence the elution of different groups of compounds where the formation of an aqueous layer over the stationary phase depends on the nature and the number of the chemically bonded groups, therefore determining the solutes' partitioning. As a result, the use of a aminopropyl column was attempted in this work to help enhance the applicability of chromatography for absorption prediction where higher reactivity and polar interactions are important characteristics of amino columns, as discussed in the literature (Gama, da Costa Silva, Collins, & Bottoli, ; Rambla‐Alegre, Carda‐Broch, & Esteve‐Romero, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So we envisaged a novel chromatography technique in which the advantages of MLC and PALC were combined to overcome the disadvantages of the two techniques. Strictly speaking, this novel separation method has been used [18][19][20] in the MLC method, yet the differences in the separation mechanisms of both are enormous. So, a better name is micellar per aqueous liquid chromatography (MPALC), to distinguish this chromatographic technique from HILIC, RPLC, PALC, and also from MLC.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Esteve-Romero et al investigated 23 seven columns including the cyano column for the determination of antibiotics by MLC, and their results showed that C 18 columns offer the best chromatographic characteristics for separation. From the dendrogram of column classication, 23 among the different brands of C 18 , C 8 and cyano columns, the cyano column was the most different. This indicated that the cyano column might have a separation mechanism which was different from MLC.…”
Section: Introductionmentioning
confidence: 99%